2022
DOI: 10.1021/acscentsci.2c00434
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Reactions over Zeolite-Based Catalysts in Syngas Conversion

Abstract: Syngas conversion can play a vital role in providing energy and chemical supplies while meeting environmental requirements as the world gradually shifts toward a net-zero. While prospects of this process cannot be doubted, there is a lingering challenge in distinct product selectivity over the bulk transitional metal catalysts. To advance research in this respect, composite catalysts comprising traditional metal catalysts and zeolites have been deployed to distinct product selectivity while suppressing side re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 133 publications
0
19
0
Order By: Relevance
“…In addition to Fe-based catalysts, the HZSM-5 zeolite is also critical for converting syngas to aromatics. , The HZSM-5 zeolite is responsible for converting lower olefins into aromatics via dehydrogenation, cyclization, aromatization, and alkylation. , The pore structure, morphology, and acidic properties determine the aromatization ability of a zeolite and the distribution of aromatic products. In recent years, a host of studies have been reported on the HZSM-5 zeolite. Table S1 compares the performances of various catalysts in syngas conversion to aromatics.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Fe-based catalysts, the HZSM-5 zeolite is also critical for converting syngas to aromatics. , The HZSM-5 zeolite is responsible for converting lower olefins into aromatics via dehydrogenation, cyclization, aromatization, and alkylation. , The pore structure, morphology, and acidic properties determine the aromatization ability of a zeolite and the distribution of aromatic products. In recent years, a host of studies have been reported on the HZSM-5 zeolite. Table S1 compares the performances of various catalysts in syngas conversion to aromatics.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent the limitation of the Fischer− Tropsch technology, bifunctional materials containing both hydrogenation (mixed metal oxide) and acidic functionality (zeotype) were developed to directly convert syngas to olefins. 4 In this process, the mechanism of olefins formation is different than Fischer−Tropsch and involves hydrogenation of CO/CO 2 to oxygenated intermediates with subsequent hydrocarbon-pool formation in the zeotype and olefin generation (via sequential alkylation and cracking of aromatic and olefinic precursors rather than polymerization of CH x species) (Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…1−3 Synthesis gas is a key platform for the transformation of nonpetroleum carbon resources into chemicals, as it can be produced from a wide variety of carbon sources, such as natural gas, coal, biomass, or (plastic) waste. 4 Given the large market share of light olefins within the high value chemicals (approximately 255 MT/yr), extensive research has been devoted to the hydrogenation of CO to light olefins. The Fischer−Tropsch process (FT) is an example of a direct route for the conversion of syngas to (light) olefins.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations